Forming the Supply Chain Strategy and Employer Brand as a Condition of Personnel Potential Development - Natalia A. Tsareva; Lolita A. Lisitca (International Journal of Supply Chain Management, 2019)
recently the supply chain employer branding strategy has gain attention in business and efficiency of jobs. It is essential deficiency of skilled staff in many fields of activity is observed. The stronger the employer brand is the stronger is the fundamental base of strategic success of the organization due to the inflow of professionals. Process of forming the employer brand is considered, instruments of realization of the personnel processes influencing forming the internal the employer brand which is a basis of economic success of the organization are offered. The cyclic model of forming the employer brand allows improving step by step the employer brand of the organization in independence of its scale and activity, thereby contributing to the development of personnel potential. Tools on diagnostics of the existing employer brand in the form of the questionnaire which is approved in the analysis of a condition of the employer brand of two holdings – medical and restaurant are developed, checked for validity. Problems in forming the employer brand of the studied organizations are revealed. Actions for strengthening of the employer brand are realized; their efficiency by means of application of the questionnaire repeatedly at an interval of one year is checked. Influence of actions for forming the employer brand on personnel capacity of the studied organizations is revealed.